Kánya Kálmán külpolitikai szemlélete (1920-1933) - Tóth, Imre (Közép-Európai Közlemények, 2015)
Kálmán Kánya came from the foreign service of the Austro-Hungarian Monarchy. He was the general secretary of the Hungarian Ministry of Foreign Affairs between 1920–1925, and also the head of that ministry with political ambitions. His leadership of the foreign apparatus reflected upon the collective frustrations of the Hungarian political upper-class after Trianon. He considered those excluded people came from the 19th century’s classic diplomacy with upstage superiority and he thought the same about his own outsider superiors. It is thought to be a highlevel of deception carry on great power politics without great power background. His views have been refined later as a foreign minister but he never considered the neighbouring, and especially the Balkan states, as equal partners.